Chapter 18 Disability in translation - Spišiaková, Eva (Taylor & Francis, 2021)
The chapter surveys the possible intersections between the fields of translation studies and disability studies. The exploration begins with an overview of the various definitions of disability, which leads to the discussion of the prominent role of the social model in present-day disability discourse. It then explores some of the issues in the translation of the rapidly changing terminology related to disability associated with the rise of disability activism since the 1970s. The chapter also surveys the existing works in the field of translation studies that relate to disability, and then highlights issues that accompany the translation of legal documents such as the UN's Convention on the Rights of Persons with Disabilities. The concluding section identifies some possible future directions for research on disability in translation studies.